2016
DOI: 10.1186/s40862-016-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of planning time on complexity, accuracy, fluency, and lexical variety in L2 descriptive writing

Abstract: This study investigates the effects of pre-task planning and online planning on L2 writing production (complexity, accuracy, fluency, and lexical variety). Seventy-eight intermediate EFL learners were randomly divided into three groups (n 1 / 3 26): pre-task planning, online planning, and no planning. Participants were required to write a description elicited through a pictorial task. Analysis of the descriptions and the results of a series of one-way ANOVA showed that the participants who completed the task u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 31 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…While Abdi Tabari's (2018) study resulted in the production of error-free clauses per sentence, the current study found no significance between the native speakers reading website and (EFC/S). To sum up, the results of the current study is consistent with (Farahani and Meraji 2011, Ghavamnia et al, 2013, Abdi-Tabari, 2016,Nosratinia and Razavi, 2016 in enhancing accuracy while writing. Comparing among the ratios of accuracy measure, it was noted that (EFT/T) was the highest ratio in improving narrative writing where it reached 2.93 while (EFC/C) was the lowest decrease in narrative writing accuracy measure where it reached 1.16.…”
Section: Discussionsupporting
confidence: 91%
“…While Abdi Tabari's (2018) study resulted in the production of error-free clauses per sentence, the current study found no significance between the native speakers reading website and (EFC/S). To sum up, the results of the current study is consistent with (Farahani and Meraji 2011, Ghavamnia et al, 2013, Abdi-Tabari, 2016,Nosratinia and Razavi, 2016 in enhancing accuracy while writing. Comparing among the ratios of accuracy measure, it was noted that (EFT/T) was the highest ratio in improving narrative writing where it reached 2.93 while (EFC/C) was the lowest decrease in narrative writing accuracy measure where it reached 1.16.…”
Section: Discussionsupporting
confidence: 91%
“…Planning time has been considered as a processing condition whose role, especially in terms of language fluency and complexity in language production, cannot be ignored. By providing planning time in performing different task types, favorable results have been gained so far (Abdi Tabari, 2016;Amadian, 2012;Ellis & Yuan, 2004;Li, Chen, & Sun, 2014;Sangarun, 2005;Tavakoli & Skehan, 2005;Wang, 2008;Yuan & Ellis, 2003). Studies with different lengths of planning time have also been conducted, such as 15 minutes (Sangarun, 2005), 10 minutes (Gilabert, 2007;Yuan & Ellis, 2003), 5 minutes (Tavakoli & Skehan, 2005), 3 minutes (Williams, 1992), and 1 minute (Mehnert, 1998).…”
Section: Studies Done On Planning Timementioning
confidence: 99%
“…Thus, it is imperative to understand what degree of learning is encouraged through learner task engagement. From a psychological standpoint, it has been theorised that learners prioritise the significance of form when they are exposed to task engagement (Tabari, 2016). Surveys such as that conducted by Kassim et al (2018) showed that specific task forms support learners to take part in cognitive procedures that improve reading comprehension.…”
Section: Introductionmentioning
confidence: 99%